Sistem Global Positioning System (GPS) Tracking Pendaki Gunung Menggunakan Komunikasi LoRa - Zaenurrohman; Arif Sumardiono; Erna Alimudin; Adrian Ramdhan; Hera Susanti (P3M Politeknik Negeri Cilacap, 2026)
Mountain climbing activities involve a high risk of hikers becoming lost due to limited location information and the lack of reliable cellular network coverage in mountainous areas. This study aims to develop an Internet of Things (IoT)-based GPS tracking system utilizing Long Range (LoRa) communication to support real-time hiker location monitoring and emergency notification in cellular network blind-spot areas. The proposed system consists of an ESP32-based transmitter equipped with a GPS module, an SX1262 LoRa module, and an emergency push button, a LoRa gateway as the receiver, and a web-based monitoring platform for real-time location visualization. System performance was evaluated through GPS accuracy testing, emergency response time measurement, and LoRa communication performance in both urban environments and the Mount Slamet hiking trail. The experimental results indicate that the GPS positioning error ranges from 7.25 to 9.16 m, with an average error of 8.25 m. The emergency notification system achieved a 100% transmission success rate with a response time of 20–22 s. Communication testing demonstrated that LoRa provided reliable data transmission over distances of up to approximately 300 m in urban environments, while communication quality degraded at longer distances due to reduced Received Signal Strength Indicator (RSSI), increased packet loss, and the effects of terrain, vegetation, and Line-of-Sight (LoS) conditions along the hiking trail. These results demonstrate that the proposed system is capable of providing reliable location monitoring and emergency communication in areas with limited cellular coverage, making it a promising solution for supporting Search and Rescue (SAR) operations in mountainous environments.